2010
DOI: 10.1038/modpathol.2010.110
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte number predicts progression of proteinuria in IgA nephropathy

Abstract: Podocyte injury is a feature of glomerulopathies associated with proteinuria, which in turn has been used as a clinical prognostic factor for glomerular diseases. The goal of this study is to investigate the relationship between podocyte injury found in biopsied renal tissue and change of proteinuria in IgA nephropathy (IgAN). In all, 35 patients with biopsy-proven IgAN and proteinuria (41.0 g per 24 h) were enrolled in the IgAN group, while 8 patients with excision of renal harmatoma or carcinoma served as ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 54 publications
(57 reference statements)
0
24
0
3
Order By: Relevance
“…Moreover, the loss of podocytes into urine contributes to the development of glomerular diseases such as proteinuria [15]. In IgA nephropathy, podocyte injury is involved in the development of proteinuria, and the loss of podocytes predicts the progression of the proteinuria [11]. Thus, we hypothesised that the increased Nestin level in urine samples from PE patients results from the loss of podocytes in the kidney, which contributes to proteinuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the loss of podocytes into urine contributes to the development of glomerular diseases such as proteinuria [15]. In IgA nephropathy, podocyte injury is involved in the development of proteinuria, and the loss of podocytes predicts the progression of the proteinuria [11]. Thus, we hypothesised that the increased Nestin level in urine samples from PE patients results from the loss of podocytes in the kidney, which contributes to proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin expression was also detected in normal and pre-eclamptic placental tissues and in endothelial cells of the chorionic villi [8]. It has been reported that the expression of Nestin in the podocytes is low in nephropathy with proteinuria [9-11]. However, the relationship between the concentration of Nestin in urine samples and the progression of PE or its role in PE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these common histologic abnormalities, other glomerular abnormalities, such as segmental sclerosis, crescent formation, and adhesion to the Bowman capsules, are detected. Podocyte loss from the GBM in IgAN may cause or contribute to the progression of proteinuria, glomerulosclerosis, and filtration failure (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Normopodocytic IgAN patients showed a significantly lower proteinuria progression rate than podocytopenic IgAN patients regardless of the comparable clinical features at biopsy and treatment regimen between the two groups. Podocyte injury is involved in development of proteinuria, and loss of podocytes predicts progression of proteinuria in IgAN [6]. More serious is that podocyte damage propagates injury by triggering secondary damage of "remnant" intact podocytes, even when the primary insult is shortlived.…”
Section: Introductionmentioning
confidence: 99%